Mesenchymal Stem Cells: An Excellent Candidate for the Treatment of Diabetes Mellitus - Qiulan Huang; Yanting Huang; Jianping Liu (International Journal of Endocrinology)
Mesenchymal stem cells (MSCs) are adult stem cells (ASCs) known for repairing damaged cells, exerting anti-inflammatory responses and producing immunoregulatory effects that can be significantly induced into insulin-producing cells (IPCs), providing an inexhaustible supply of functional β cells for cell replacement therapy and disease modeling for diabetes. MSC therapy may be the most promising strategy for diabetes mellitus because of these significant merits. In this paper, we focused on MSC therapy for diabetes.